2015
DOI: 10.1001/jamaneurol.2015.0941
|View full text |Cite|
|
Sign up to set email alerts
|

Neuroinflammation in Temporal Lobe Epilepsy Measured Using Positron Emission Tomographic Imaging of Translocator Protein

Abstract: IMPORTANCE Neuroinflammation may play a role in epilepsy. Translocator protein 18 kDa (TSPO), a biomarker of neuroinflammation, is overexpressed on activated microglia and reactive astrocytes. A preliminary positron emission tomographic (PET) imaging study using carbon 11 ([ 11 C])-labeled PBR28 in patients with temporal lobe epilepsy (TLE) found increased TSPO ipsilateral to seizure foci. Full quantitation of TSPO in vivo is needed to detect widespread inflammation in the epileptic brain. OBJECTIVES To deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
149
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(156 citation statements)
references
References 31 publications
4
149
1
2
Order By: Relevance
“…53 However, these approaches will render only relative rather than absolute differences or changes and thus require a hypothesis that only specific regions of the brain are affected, which may not be the case even in disorders with a presumed circumscribed pathology. 54 In the present study, we hypothesized that both global and potentially local changes would be present in brain after surgery and we therefore performed full kinetic modeling, to obtain V T values.It may be argued that residual effects of anesthetic agents can contribute to the reduction in glial activity on the 3rd to 4th postoperative day. Although clinical studies on this topic are scarce, an acute reduction of [ 11 C]PBR28 binding has been reported in humans after propofol administration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…53 However, these approaches will render only relative rather than absolute differences or changes and thus require a hypothesis that only specific regions of the brain are affected, which may not be the case even in disorders with a presumed circumscribed pathology. 54 In the present study, we hypothesized that both global and potentially local changes would be present in brain after surgery and we therefore performed full kinetic modeling, to obtain V T values.It may be argued that residual effects of anesthetic agents can contribute to the reduction in glial activity on the 3rd to 4th postoperative day. Although clinical studies on this topic are scarce, an acute reduction of [ 11 C]PBR28 binding has been reported in humans after propofol administration.…”
mentioning
confidence: 99%
“…53 However, these approaches will render only relative rather than absolute differences or changes and thus require a hypothesis that only specific regions of the brain are affected, which may not be the case even in disorders with a presumed circumscribed pathology. 54 In the present study, we hypothesized that both global and potentially local changes would be present in brain after surgery and we therefore performed full kinetic modeling, to obtain V T values.…”
mentioning
confidence: 99%
“…The translocator protein (TSPO), also known as the peripheral benzodiazepine receptor, is upregulated by activated microglia and macrophages and thus represents a suitable target for PET imaging of neuroinflammation after brain insults (11). PET imaging in TLE patients identified increased TSPO binding of the radioligand 11 C-PBR28 in temporal structures both ipsilateral and contralateral to the seizure focus (12). Initial PET imaging studies in a post-SE rat model have revealed elevated distribution volume of the TSPO radiotracer 18 F-PBR111 in epilepsyassociated brain regions, such as the hippocampus and the amygdala, at 1-6 wk after kainate-induced SE (8,13).…”
mentioning
confidence: 99%
“…V T /f p ) (e.g. [42]). However, accurate measurement of the free fraction (f p ) is difficult, and errors in f p may increase the variability in corrected V T (V T /f p ) [44].…”
Section: Challenges Of Second-generation Tspo Pet Radioligandsmentioning
confidence: 99%